Association between Spinopelvic Alignment and Lumbar Intervertebral Disc Degeneration Quantified with Magnetic Resonance Imaging T2 Mapping in Patients with Chronic Low Back Pain - Izaya Ogon (Spine Surgery and Related Research, 2020)
Introduction: Although intervertebral disc degeneration (IVDD) and spinopelvic malalignment are likely key structural features of spinal degeneration and chronic low back pain (CLBP), the correlation analysis has not been fully conducted. This cross-sectional quantitative magnetic resonance imaging (MRI) T2 mapping study aimed to elucidate the association between IVDD and spinopelvic alignment in CLBP patients. Methods: The subjects included 45 CLBP patients (19 men and 26 women; mean age, 63.8 ± 2.0 years; range, 41-79 years). The T2 values of the anterior annulus fibrosus (AF), the nucleus pulposus (NP), and the posterior AF were evaluated using MRI T2 mapping. We compared the possible correlations of spinopelvic parameters with T2 values of anterior AF, NP, and posterior AF using Pearson's correlation coefficient analysis. T2 values in these regions were classified into upper (L1-L2 and L2-L3), middle (L3-L4), and lower (L4-L5 and L5-S1) disc levels, and we analyzed the correlations with spinopelvic parameters. Results: There were significant correlations of the anterior AF T2 values with lumbar lordosis (r = 0.51, p < 0.01), sacral slope (r = 0.43, p < 0.01), sagittal vertical axis (r = −0.40, p < 0.01), and pelvic tilt (r = −0.33, p < 0.01). In all lumbar levels, T2 values of anterior AF had significantly positive correlation with LL and significantly negative correlation with SVA. In lower disc level, T2 values of anterior AF had significantly positive correlation with SS and significantly negative correlation with PT. T2 values of NP and posterior AF had no significant correlations with spinopelvic parameters in all lumbar disc levels. Conclusions: In summary, this study indicated that the anterior AF degeneration is associated with hypolordosis of the lumbar spine, anterior translation of the body trunk, and posterior inclination of the pelvis in CLBP. Anterior AF degeneration in all lumbar disc levels was associated with hypolordosis of the lumbar spine and anterior translation of the body trunk. Anterior AF degeneration in lower disc level was associated with posterior inclination of the pelvis.